Novel, clinically relevant genomic patterns identified by comprehensive genomic profiling in ATRX-deficient IDH-wildtype adult high-grade gliomas - Gábor Bedics; Péter Szőke; Bence Bátai; Tibor Nagy; Gergő Papp; Noémi Kránitz; Hajnalka Rajnai; Lilla Reiniger; Csaba Bödör; Bálint Scheich (Scientific Reports, 2023)
Abstract Glioblastomas are the most common IDH-wildtype adult high-grade gliomas, frequently harboring mutations in the TERT gene promoter (pTERT) and utilizing the subsequent telomerase overexpression for telomere length maintenance. However, some rare cases show loss of ATRX and use alternative mechanisms of telomere lengthening. In this study, we performed the first complex genomic analysis specifically concentrating on the latter subgroup. Comprehensive genomic profiling of 12 ATRX-deficient and 13 ATRX-intact IDH-wildtype adult high-grade gliomas revealed that ATRX and pTERT mutations are mutually exclusive. DNMT3A alterations were confined to ATRX-deficient, while PTEN mutations to ATRX-intact cases. RAS–MAPK pathway alterations, including NF1 mutations, were more characteristic in the ATRX-deficient group. Variants of genes related to homologous recombination repair showed different patterns of affected genes. Two ATRX-deficient tumors with high tumor mutational burden and mismatch repair deficiency were found. One of these contained a novel fusion involving the NTRK2 and LRRFIP2 genes, while the other showed loss of MSH2 and MSH6 without genetic alterations in the encoding genes suggesting an epigenetic background. Genetic characteristics of ATRX-deficient IDH-wildtype adult high-grade gliomas suggest that these tumors are particularly intriguing targets of potential future therapeutic interventions including immunotherapies combined with MAPK pathway inhibition and DNA repair inhibitors.